An exploration of the knowledge, experiences, and practices of staff towards Fetal Alcohol Spectrum Disorder (FASD) in an Aotearoa New Zealand prison context : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatu, New Zealand - Kawana, Kahlia (Massey University, 2023)
Fetal alcohol spectrum disorder (FASD) is a neurodevelopmental disability that occurs through prenatal alcohol exposure. The disability leads to life-long cognitive, behavioural, learning, social, and physical deficits that occur along a spectrum of severity. The heterogeneous manifestation of FASD means diagnosis is extremely challenging, contributing to the lack of accurate, up-to-date prevalence statistics for both local and global communities. Although there are a lack of prevalence statistics, current research estimates suggest FASD is very common in Corrections settings, however prison staff remain largely uneducated and unaware of how to appropriately identify, manage, and support prisoners with FASD. This thesis explored the knowledge, experiences, and practices regarding FASD for prison staff at Auckland South Corrections Facility (ASCF) in Aotearoa New Zealand. The project was conducted in collaboration with ASCF to identify gaps in staff knowledge and inform more effective practice with FASD-affected prisoners. This research was conducted within a qualitative framework with a realist/essentialist epistemology. 16 staff members from Custody, Health, Case Management, Education, the Cultural team, and Psychology departments participated in semi-structured interviews. The data was analysed using Thematic Analysis, focusing on semantic content. Several themes were identified based on interpretations of participant responses. Overall, there was limited awareness of FASD among participants. This lack of awareness was largely due to the unavailability of FASD-related training for staff and problems with internal information sharing systems. Lack of staff awareness was shown to increase vulnerability and reduce access to rehabilitative services for affected prisoners. Participants expressed a willingness to learn more about FASD and adapt their practice to support the needs of prisoners who were suspected or confirmed of having this disability. This reflected a wider organisational culture that was dedicated to innovation and reducing the reoffending of prisoners. Key findings from the research suggest that inclusion of formal FASD-related training for staff and improvements in the way FASD related information is shared within the institution, including a formal process for sharing this information can improve staff awareness and outcomes for prisoners. More research considering the prevalence of FASD in the Aotearoa New Zealand prison context is needed to increase visibility and ensure resources are dedicated to understanding and managing this disability in prisons.
Keywords: 520199 Applied and developmental psychology not elsewhere classified